In vivo anti-aging properties on fat diet-induced high fat Drosophila melanogaster of n-butanol extract from Paecilomyces hepiali - Akang Dan; Yushi Chen; Yongqi Tian; Shaoyun Wang (Food Science and Human Wellness)
The purpose of this study was to explore the potential of the development and application of Paecilomyces hepiali, a fungus with edible and medicinal value, as a foodborne antioxidant and anti-aging agent. Its n-butanol extract (PHE) from rice cultures was selected for anti-aging experiment because of significant free radical scavenging activity in vitro. In vivo, PHE could significantly prolong the mean lifespan, 50 % survival days, and the maximum lifespan of Drosophila on a high-fat diet. It is amazing that the mean lifespan increased from 19.1 days to 32.9 days, 50 % survival days increased from 15.7 days to 34.3 days, and the maximum lifespan extended from 44.7 days to 52.7 days, when the high-fat female Drosophila model was fed with 10 μg/mL PHE. Further research showed that PHE reduced the accumulation of peroxide products and increased the activity of antioxidant enzymes. Then, through antioxidant activity tracking, dimerumic acid (compound 1, the IC50 value of 3.4 μg/mL on DPPH free radicals scavenging activity), 4,5-dihydroxy-3-methoxypentanoic acid (compound 2, new compound), and thymidine (compound 3) were isolated from PHE. It is worth mentioning that dimerumic acid, the major antioxidant compound of PHE (content up to 3 %), was discovered in P. hepiali for the first time. It was concluded that PHE showed excellent anti-aging activity at a very low concentration on fat diet-induced high fat Drosophila melanogaster, and dimerumic acid may be its main material basis. These results indicated that PHE had the potential to be developed as antioxidant and anti-aging agent in the healthcare industry.